Implementation of Human Resource Development Strategies in Improving Employee Motivation and Work Effectiveness - Ainur, Emilia; Mubarrok, Ujang Syahrul (Almana : Jurnal Manajemen dan Bisnis, 2024)
In the face of increasingly intense competition in the business world, quality human resources (HR) are the main factor for companies to survive and compete. In this case, the workforce is an important asset owned by the company and has a big role in determining the company's success. Human resource development (HRD) is a crucial element for companies in improving the skills of each employee so that the work done can be more effective and efficient. This study aims to analyze the implementation of human resource development strategies in increasing work motivation and employee work effectiveness at CV Medali Mas Kota Kediri. The background of this research is related to the importance of human resource development in the ikat weaving industry to increase the competitiveness of the company. The method used is descriptive qualitative with interviews, observation, and documentation as data collection techniques. The results showed that the human resource development strategies implemented by CV Medali Mas, such as technical training, soft skills development, and performance awards succeeded in increasing employee motivation. Motivation contributes to increased work effectiveness which is reflected in increased productivity, work quality, and timeliness of employees in completing tasks.